ENT 530 Social Media Portfolio: PENDI DSGN / Afandi Aqmal Abdullah - Abdullah, Afandi Aqmal (2021)
PENDI (Clothing business): Starting a business for PENDI products is stickers, which is to produce more stylish, funky, and even black metal sticker designs. With the existing advantages, by striving to grow the business, PENDI's business produces new products, namely t-shirts to be used as a place to develop the brand by producing a simple, stylish, dark style and also a variety of unique design concepts. It was established in 2019, while still studying at UITM Kota Samarahan. Due to problems in time management, the business had to close temporarily on the pretext of wanting to focus on other careers first. Finally, with the opportunities available now, the business is also striving to grow in terms of marketing strategy and design to be featured to customers.